2014
DOI: 10.1007/s00421-014-2989-4
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial functional changes following short-term exercise training

Abstract: LA function assessed by STE improves rapidly during short-term intensive exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…The results led to two main findings: first, we observed that both regimens of CT elicited favorable effects on the LA Correlation between the changes in the systolic blood pressure and in PALS in patients undergoing supervised exercise (CTLF + CTHF). (29). Conversely, no changes or small reductions in reservoir strain were described in athletes (30,31).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results led to two main findings: first, we observed that both regimens of CT elicited favorable effects on the LA Correlation between the changes in the systolic blood pressure and in PALS in patients undergoing supervised exercise (CTLF + CTHF). (29). Conversely, no changes or small reductions in reservoir strain were described in athletes (30,31).…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the first point, the LA adaptations to exercise training have been assessed mainly in healthy subjects and athletes, while very few studies on this topic have previously been conducted in patients with cardiovascular diseases. In sedentary healthy individuals, increases in the LA strain parameters have been observed after short exercise training interventions without any detectable change in the LA size ( 29 ). Conversely, no changes or small reductions in reservoir strain were described in athletes ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their training protocol consisted of running and walking on a treadmill, which was one of the limitations of their study in that HIIT and CMT had not been offered under isocaloric conditions. The training intensity during the 16-week period should be controlled by determining VO 2 max and the maximum heart rate to apply an accurate intensity and allow its efficiency to be examined through retest [ 29 ]. In addition, the training intensity in the study from Scharf et al was greater than that of the present research (calculated based on the maximum heart rate).…”
Section: Discussionmentioning
confidence: 99%
“…As the teleoperated systems permeate surgery, they showcase numerous benefits compared to traditional methods [46,47]. As a result, many procedures have been converted from laparoscopic surgery to RAMIS, from cancer removal to partial organ resection [48,49,50,51,52,53,54,55,56,57,58,59,60]. As it emerges from all these studies, RAMIS represents a significant upgrade to laparoscopic surgery.…”
Section: Palpation and Remote Palpationmentioning
confidence: 99%